Possible Common Origin of B Chromosomes in Neotropical Fish (Siluriformes, Auchenipteridae) Reinforced by Repetitive DNA Mapping - Lui,Roberto Laridondo (2021)
Abstract The aim of this paper was to present the second case of B chromosomes in Auchenipteridae (Trachelyopterus sp.), and to test the hypothesis that the B chromosomes of this species and Parauchenipterus galeatus might have a common origin, since these two species have phylogenetic proximity. Both species have 58 chromosomes in the A complement, heterochromatin preferentially located at terminal region of the most of chromosomes, simple Ag-NORs located at the short arm of a subtelocentric pair, which was confirmed by hybridization with 18S rDNA, two submetacentric pairs carrying 5S rDNA sites, and presence of B chromosomes. The B chromosomes of the two species are small, metacentric, and almost totally heterochromatic, with variation of number intra and interindividual. In addition, for the first time in fish, the telomeric sequence [TTAGGG]n was dispersed along the B chromosomes (both species). The [GATA]n microsatellite were scattered in all chromosomes of the A complement and absent in the B chromosomes, in both species. These aspects confirm the phylogenetic proximity between the genus Parauchenipterus and Trachelyopterus, and they suggest the hypothesis that the B chromosomes of the two species might have common origin, previous to the diversification of these genera.